Expression of DGAT2 Gene and Its Associations With Intramuscular Fat Content and Breast Muscle Fiber Characteristics in Domestic Pigeons (Columba livia) - Mao, Haiguang; Yin, Zhaozheng; Wang, Mengting; Zhang, Wenwen; Raza, Sayed Haidar Abbas; Althobaiti, Fayez; Qi, Lili; Wang, Jinbo (Frontiers in Veterinary Science, 2022)
Diacylglycerol acyltransferase 2 (DGAT2) catalyzes the final step in triglyceride synthesis and plays an important role in the synthesis of fat, but its expression effects on intramuscular fat content and muscle development are still unknown. In this study, we investigated the expression of DGAT2 gene and its associations with intramuscular fat content and breast muscle fiber characteristics in pigeons. The spatio-temporal expression profile of pigeon DGAT2 gene in breast muscle showed that the mRNA expression level of DGAT2 gene in subcutaneous fat showed the highest (P<0.01) among eight tissues from 0w to 4w of age, and showed an upward trend week by week, followed by liver (P<0.05). Moreover, both mRNA and protein levels of DGAT2 gene in breast muscle showed an upward trend from 0w to 4w (P<0.05), accompanied by the up-regulation of MYOD1 and MSTN. In addition, the paraffin sections analysis results revealed that the diameter and cross-sectional area of pectoralis muscle fiber significantly increased with age (P < 0.05), and a significant positive correlation was shown between the DGAT2 gene expression level and muscle fiber diameter (P < 0.05). Furthermore, correlation analysis suggested that the mRNA expression level of pigeon DGAT2 gene was significantly (P<0.01) correlated with intramuscular fat content in breast muscle. These results implied that DGAT2 gene has a close relationship with intramuscular fat content and breast muscle fiber characteristics in pigeons, indicating that DGAT2 gene might be used as a candidate gene marker-assisted breeding in pigeons.